Antarctic springtime measurements of ozone, nitrogen dioxide, and aerosol extinction by SAM II, SAGE, and SAGE II - Mccormick, M. P.; Larsen, J. C. (1986)
Simultaneous vertical profiles of O3, NO2, and aerosol extinction obtained with the Stratospheric Aerosol Measurement II, Stratospheric Aerosol and Gas Experiment (SAGE), and SAGE II satellite instruments across the southern polar vortex show that significant differences exist at all altitudes. Both gaseous species display lower concentrations within the vortex over measurement altitudes ranging from the tropopause to 60 km and 20 to 40 km for O3 and NO2, respectively. Aerosol extinction above 15-18 km and total aerosol stratospheric column are also lower inside the vortex than outside. Total column amounts of O3 and NO2 are found to be strongly coupled to spatial location within the vortex, with minimum total values located around the vortex center. Vertical profiles selected to emphasize the observed difference across the circumpolar vortex are presented for October 13, 1981, and October 13, 1985, near 70 and 68 deg S latitude, respectively.